Co-expression of LPHN3 and NKX3.1 as a predictive biomarker for metastasis in breast cancer - Khan, Ramsha; Alamgir, Mohiuddin; Khan, Nehad; Khan, Mohammad Bilal; Abbas, Farah Fatima; Kamil, Saba (Journal of the Pakistan Medical Association, 2025)
Objectives: To assess latrophilin-3 (LPHN3) and Homeobox protein (NKX- 3.1) protein expression in breast cancer, and the association with metastasis. Method: The case-control was conducted at the Dow University of Health Sciences, Karachi, and comprised breast carcinoma tissue sections diagnosed between July and November 2022. The tissues were divided into 2 equal groups, with group A having cases with metastasis and group B having controls without metastasis. expression of latrophilin-3 and NKX3.1 in tissue was assessed using immunohistochemistry in both the groups. Data was analysed using SPSS 21. Results: Of the 80 women with mean age 50±1.20 years, 40(50%) were in each of the 2 groups. Overall, 31(38.8%) tissues were from the right-side breast, and 49(61.2%) were from the left-side breast. Latrophilin-3 was highly expressed in group A 35(87.5%) compared to group B 10(25%) (p<0.001). The expression of NKX3.1 was weak in 10(25%) group A cases and 4(10%) group B controls (p=0.070). Conclusions: The expression of latrophilin-3 could play an important role in the prediction of metastasis in early-stage breast cancers. In contrast, NKX3.1 expression had no significant association with metastasis. Key Words: Immunohistochemistry, LPHN3, NKX3.1, Breast cancer, Metastasis.